Institutional impacts on corporate social responsibility: A comparative analysis of New Zealand and Pakistan - Majid Khan; James C. Lockhart; Ralph Bathurst (International Journal of Corporate Social Responsibility (JCSR), 2018)
This study explores the relationship between institutional mechanisms and corporate social responsibility (CSR) in both Pakistan and New Zealand. Institutional factors are normally categorised as being either formal or informal. It is argued that a combination of formal institutions and informal institutions in any jurisdiction shape the adoption, or otherwise of CSR by business through its adherence to acceptable governance praxis. Corporate regulation in Pakistan is heavily influenced from elsewhere, especially from British common law. By contrast the institutional realities produce remarkably different outcomes in the two jurisdictions. This study examines which formal and informal institutions influence CSR disclosures, in that businesses disclose CSR practices in response to regulations; cognitive pressures that help people understand and interpret the practice correctly; and, cultural values enforcing the same practice. Quantitative content analyses of a sample of eight listed companies' annual reports were completed from each country. Reporting and disclosure practices were identified in both. Underlying institutions were then recorded as being recognised, acknowledged or inferred by the respective reporting business. The results highlighted that Pakistani companies disclose more about CSR than those analysed from New Zealand. This result is attributed to the recently developed corporate governance guidelines by the Securities and Exchange Commission of Pakistan. The informal national institutions in both countries also play a vital role in the disparity of disclosures. This is not to suggest that New Zealand listed companies lag behind those in Pakistan with respect to their contribution to CSR initiatives, simply that the disclosure levels between the two favour those companies in Pakistan.
Keywords: 650; Corporate social responsibility; Corporate governance; Regulation; Institutional theory; New Zealand; Pakistan